A study to investigate the anti-methanogenic properties of black tea waste in dairy cows in order to achieve a cleaner environment - Kaya , A; Kaya , A; Palangi, V; Kaya , H; Macit , M (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, the authors substituted alfalfa hay with factory black tea waste (FBTW) in dairy cattle total mixed ration (TMR) and subsequently tested its effects on in-vitro carbon dioxide and methane production, metabolizable energy (ME), organic matter digestibility (OMD), net energy lactation (NEL), microbial protein production (MP) and Daisy incubator digestibility parame-ters. Experimental diets included 0% (TW0), 25% (TW1), 50% (TW2) and 75% (TW3) FBTW sub-stituted alfalfa hay in dairy cattle TMR rations. Substitution of alfalfa hay with FBTW in TMR linearly decreased in-vitro GP, methane, ME, NEL and OMD values (P<0.05), and linearly in-creased true dry matter digestibility (TDMD), partition factor (PF) and microbial protein pro-duction efficiency (MPSE) values (p<0.05). Organic matter (IVOMD), in-vitro true dry matter (IVTDMD), and NDF digestibility (IVNDFD) values, determined in the Daisy II incubator, were decreased by substituting FBTW for alfalfa hay in TMR (p<0.05). Substitution of alfalfa hay by FBTW up to 50% in TMR as an alternative roughage source in ruminant animal nutrition can be beneficial yet in-vivo studies are required for a solid conclusion.